Costs, and cost-outcome of school feeding programmes and feeding programmes for young children. Evidence and recommendations. (May 2016) - Kristjansson, E.A.; Gelli, A.; Welch, V.; Greenhalgh, T.; Liberato, S.; Francis, D.; Espejo, F.
Abstract: Our objectives for this study were to provide updated, realistic data on the costs and cost-outcomes of school feeding in Low and Middle Income Countries. We also aimed to identify factors that may influence effectiveness and therefore, cost effectiveness of the interventions. To do this, we combined data on effect sizes for physical and psychosocial outcomes from two Cochrane systematic reviews with new data on the costs of school feeding. We simulated the costs of preschool feeding based on the school feeding costs. We found that he average for low- and middle-income countries combined was US$72, with large variations across countries. We also found a wide variation in costs for different outcomes. We suggest several ways in which effectiveness may be improved and cost-per outcome lowered for both programmes.